2013
DOI: 10.1007/s11481-013-9443-y
|View full text |Cite
|
Sign up to set email alerts
|

Drug Induced Increases in CNS Dopamine Alter Monocyte, Macrophage and T Cell Functions: Implications for HAND

Abstract: Central nervous system (CNS) complications resulting from HIV infection remain a major public health problem as individuals live longer due to the success of combined antiretroviral therapy (cART). As many as 70% of HIV infected people have HIV associated neurocognitive disorders (HAND). Many HIV infected individuals abuse drugs, such as cocaine, heroin or methamphetamine, that may be important cofactors in the development of HIV CNS disease. Despite different mechanisms of action, all drugs of abuse increase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
37
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(47 citation statements)
references
References 261 publications
1
37
0
3
Order By: Relevance
“…Addictive psychostimulants increase extracellular dopamine in select dopaminergic neuroanatomic structures in the CNS (Di Chiara and Bassareo 2007; Gaskill et al 2013). The circulating CD14+/CD16+ monocyte subpopulation plays a critical role in HIV neuropathogenesis (Ellery et al 2007; Fischer-Smith et al 2008; Buckner et al 2011).…”
Section: Neuropathologymentioning
confidence: 99%
“…Addictive psychostimulants increase extracellular dopamine in select dopaminergic neuroanatomic structures in the CNS (Di Chiara and Bassareo 2007; Gaskill et al 2013). The circulating CD14+/CD16+ monocyte subpopulation plays a critical role in HIV neuropathogenesis (Ellery et al 2007; Fischer-Smith et al 2008; Buckner et al 2011).…”
Section: Neuropathologymentioning
confidence: 99%
“…Finally, we will discuss the unanswered questions on the synergy between METH and HIV/AIDS as part of the future prospective. The impact of METH abuse on neurological manifestations of HIV-1 infected and un-infected patients has been extensively reviewed in recent years [1315], therefore will not be covered in this review.…”
Section: Introductionmentioning
confidence: 99%
“…In vitro studies have demonstrated that cocaine increases HIV-1 replication in PBMCs (Peterson et al 1991), CD4+T cells (Pandhare et al 2014), macrophages (Dhillon et al 2007; Gaskill et al 2009; Gaskill et al 2013) , microglia (Gekker et al 2004; Gekker et al 2006) and potentiates astrocyte toxicity after activation by HIV-1 gp120 (Yao et al 2010). Proteomics analyses have revealed the enhancement of HIV-replication in normal human astrocytes after exposure to cocaine (Reynolds et al 2006).…”
Section: Introductionmentioning
confidence: 99%